Evaluation of pre-pulse inhibition of the post auricular muscle reflex as an indicator for the presence of tinnitus - Wilson, Caroline (2018)
Gap-induced pre-pulse inhibition of the acoustic startle (GPIAS) is a behavioural test for tinnitus in animals. It relies on a short gap in a continuous background noise which provides a cue to the loud startling stimulus which follows. As a result, gap conditions demonstrate an inhibition of the response to the startling stimulus compared to no-gap conditions. The disrupting effect of tinnitus on the normal GPIAS has been shown in a number of species, including in humans. Such disruption was originally thought to be caused by tinnitus ‘filling in’ the gap, but recent studies have challenged this explanation. Preliminary work in humans measuring the eye blink reflex showed gap detection deficits in tinnitus subjects, but the underlying mechanisms of this effect are unclear. The eye blink response has a relatively long latency (>40ms) and therefore is not a simple primary reflex, nor is it specifically related to the auditory system.